Management and socio-economic conditions of fishermen of the Baluhar Baor, Jhenaidah, Bangladesh - Abdullah-Bin-Farid, BM Shahriar; Mondal, Shuvagato; Satu, Kulsum Akter; Adhikary, Ripon Kumar; Saha, Debasish (Journal of Fisheries, 2013)
This study was conducted on the management of the Baluhar Baor and fishermen’s socio-economic conditions of the baor in Jhenaidah district, Bangladesh. Data were collected by interviews, FGDs and CIs with key informants. This baor was managed under Oxbow Lake Project-1 of Department of Fisheries of Bangladesh government. Hypophthalmichthys molitrix, Labeo rohita, Catla catla, Cirrhina cirrhosus, Cyprinus carpio and Ctenopharyngodon idella were commonly stocked at the composition of 34%, 13%, 12%, 12%, 15% and 14%, respectively. Kochal, komor and chack fishing were used for harvesting and yearly production was 750 kg/ha. While studying the socio-economics, 58% fishermen were lived in joint families. 78% fishermen used kancha sanitary latrine which reflects their poor hygienic condition but they used tubewell for drinking water. 58% fishermen were with 0.041 hectare lands and 74% lived in kancha house. The annual income varied from BDT 15,000 to 60,000. Education level was found very low and only 18% completed their primary education. Majority fishermen (82%) visited village doctor for health services due to low income and lack of knowledge. All fishermen were fully dependent on baor fishery for their livelihood. It is possible to uplift their socio-economic by managing the baor with improved technology.